The effect of brainstorming strategies in developing the skill of employing reading text in solving problems among third grade intermediate students - Al-Dosari, Mashael Saleh; Al-Braiqi, Rashed Omar Ali (Journal of Curriculum and Teaching Methodology, 2022)
The aim of the research is to reveal the impact of the use of brainstorming strategy in the development of the skill of employing the reader in solving problems in the third grade middle school, in Jeddah governorate during the second semester of 1443 Ah, and the researchers used the experimental curriculum with semi-experimental design, and to achieve that goal the researchers prepared tools and research materials, and the tool was in the list of skills of employing the reader in problem solving, the teacher’s guide, and the test of the skill of employing the reader in solving problems, and applied to a sample consisting of (60) students From the third grade, it was divided into two groups: an officer (30) students, and a pilot (30) students, and the results showed differences between the average of the two experimental groups with a total average (19.57), as opposed to the female officer’s average (11.23) in the performance test. The dimension in the skill of employing the reader in problem solving, and the differences are statistically significant at the level of significance (α≤0.05) in favor of the experimental group studied by brainstorming strategy, the size of the effect according to the ETA box (0.75), indicates the effect (significant), and based on the recommended results Researchers: By employing brainstorming strategy in reading education, taking advantage of the guideline for the use of brainstorming strategy, taking care to include the skills of employing the reader in solving problems, and strengthening them in the Arabic language curriculum.